Low-loss power management strategy for weak and low-frequency biomechanical energy harvesting for new generation wearable electronics - Li, Weilu; Huang, Yongcan; Liu, Chunhua; Valencia, Agnes; Daoud, Walid A. (Frontiers in Electronics, 2025)
IntroductionAmidst the rapidly growing development of wearable electronics, their dependence on external power sources increases the power expense while leading to interruptions of their operation during charging. Biomechanical energy harvesters offer a promising solution for self-powered wearable electronics by converting waste kinetic energy to electricity. Despite successful efforts in advancing their power outputs from μW to mW, several challenges persist, including low output current at the μA-level, high internal impedance in the GΩ-level, and AC outputs, restricting their practical applications. Conventional power management circuits are commonly utilized in high-frequency harvesters without adequate consideration of the energy loss that incurs, potentially leading to circuit failure when used in low-frequency harvesters with a lower power output.MethodsHere, we introduce a low-loss power management circuit (L-PMC) that functions under low-frequency conditions to facilitate biomechanical energy harvesting.ResultsOur innovative two-stage energy transfer strategy boosts the energy extraction efficiency to 42.24%, breaking previous records. With an energy transfer efficiency of 30.59%, L-PMC can charge a battery from 1.9 V to 2.4 V in just 10 min.DiscussionMoreover, the integration of passive current amplification tripled charge accumulation and energy storage, representing 207% enhancement in energy transfer efficiency, presenting a versatile and universal approach to low-frequency biomechanical energy harvesting for new generation wearable electronics.